2017
DOI: 10.18632/oncotarget.21973
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of STAT3/VEGF/CDK2 axis signaling is critically involved in the antiangiogenic and apoptotic effects of arsenic herbal mixture PROS in non-small lung cancer cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…Thus, the underlying mechanisms, such as whether β-elemene inhibits the upstream molecules of Stat3 resulting affected Stat3-associated signaling, remain inconclusive, and more experiments are still needed to elucidate them. In accordance with this, inactivation and inhibition of Stat3 signaling have been shown to be involved in the inhibition of cell growth and progression in several cancer types, including lung cancer 10 , 51 53 . This finding suggested that targeting Stat3 could be used in lung cancer treatment.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, the underlying mechanisms, such as whether β-elemene inhibits the upstream molecules of Stat3 resulting affected Stat3-associated signaling, remain inconclusive, and more experiments are still needed to elucidate them. In accordance with this, inactivation and inhibition of Stat3 signaling have been shown to be involved in the inhibition of cell growth and progression in several cancer types, including lung cancer 10 , 51 53 . This finding suggested that targeting Stat3 could be used in lung cancer treatment.…”
Section: Discussionsupporting
confidence: 54%
“…Scholars have confirmed that salvianolic acid B can have a role in improving cognition and promoting angiogenesis by activating p-STAT3 to produce VEGF-A (23). Inhibition of the STAT3/VEGF-A pathway in vectors for non-small cell lung cancer would inhibit angiogenesis and promote tumor cell apoptosis (24). Taken together, the evidence suggests that STAT3 is, perhaps, not only downstream of IL-9/IL-9R but also an upstream molecule of VEGF-A.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HG promotes the expression of VEGF by activating STAT3 in non-small lung cancer cells [33], suggesting that the effects of GLUT4 on VEGF may also be dependent on STAT3 activation. Of note, our results suggest that the regulation of HG, estrogen and GLUT4 on VEGF may also contribute to the progression of UEC by stimulating angiogenesis.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%